2023
DOI: 10.1249/mss.0000000000003141
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Acute Ketone Monoester Ingestion on Cardiorespiratory Responses to Exercise and the Influence of Blood Acidosis

Abstract: Ketone monoester (KE) ingestion can induce hyperketonemia and blood acidosis. We previously found that acute ingestion of 0.6 g·kg−1 body mass KE increased exercise heart rate (HR) compared with placebo.PurposeThis study aimed to examine the effect of KE ingestion on exercise cardiac output (Q˙) and the influence of blood acidosis. We hypothesized that KE versus placebo ingestion would increase Q˙, and coingestion of the pH buffer bicarbonate would mitigate this effect.MethodsIn a randomized, double-blind, cro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
2
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 47 publications
(84 reference statements)
0
2
1
Order By: Relevance
“…The present study found that in a trained female cohort, the acute ingestion of KME + CHO elicited similar 10-km TT completion times, average power output, and session RPE compared with CHO alone. Additionally, the responses observed between conditions in HR and RPE across the GXT intervals and each respective kilometer did not differ significantly, which are in contrast to more recent findings (24,25). These data were observed during the GXT despite significantly elevated βHB concentrations and lower glucose and lactate concentrations across the KME + CHO condition.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…The present study found that in a trained female cohort, the acute ingestion of KME + CHO elicited similar 10-km TT completion times, average power output, and session RPE compared with CHO alone. Additionally, the responses observed between conditions in HR and RPE across the GXT intervals and each respective kilometer did not differ significantly, which are in contrast to more recent findings (24,25). These data were observed during the GXT despite significantly elevated βHB concentrations and lower glucose and lactate concentrations across the KME + CHO condition.…”
Section: Discussioncontrasting
confidence: 99%
“…In fact, the seminal study conducted by Cox et al (5) demonstrated that the ingestion of a carbohydrate beverage with the (R)-1,3-hydroxybutyl R-3-hydroxybutrate KME did indeed lower glycolytic intermediates, although an improvement was still observed in cycling performance (~2%). Since then, studies incorporating various exogenous ketone esters with CHO or alone tend to demonstrate null findings in markers of performance (9,24,26–30) or a decrement to performance (25,31,32). Similarly, the present study demonstrated no benefits to physical performance with KME + CHO ingestion compared with CHO alone in a female cohort.…”
Section: Discussionmentioning
confidence: 99%
“…The lower HR during the time trial after KE ingestion may relate to effects of KE ingestion on peak HR and/or perceived exertion or reflect the lower time-trial power output. Interpreting these HR data are challenging because ingestion of 0.6 g/kg KE increased HR during submaximal cycling at a constant workload that was equivalent to ventilatory threshold intensity (McCarthy et al, 2021(McCarthy et al, , 2023. It is unknown whether the comparatively lower dose of KE used in the current study would similarly affect exercise HR or whether HR responses to KE ingestion differ depending on relative exercise intensity.…”
Section: Discussionmentioning
confidence: 89%